Anxiolytic effects of vestipitant in a sub-group of healthy volunteers known to be sensitive to CO2 challenge. (May 2014) - Poma, Stefano Zanone; Merlo-Pich, Emilio; Bettica, Paolo; Bani, Massimo; Fina, Paolo; Ziviani, Luigi; Milleri, Stefano
The pharmacological properties of two NK1 antagonists were studied in comparison with a benzodiazepine during a 7% CO2 challenge in a population of healthy volunteers selected for a high sensitivity to the challenge. In total, 19 healthy subjects, pre-screened for their responsiveness to the 7% CO2 test, took part in the randomised, double-blind, cross-over, incomplete block design study. After receiving treatment or placebo, the volunteers were subjected to three 7% CO2 challenges each for a time of 20 min. The treatment consisted of the administration of the following three active drugs: a single dose of benzodiazepine alprazolam (0.75 mg) and a single dose of the NK1 antagonists vestipitant (GW597599) (15 mg) and vofopitant (GR205171) (25 mg). Anxiety during the challenge was evaluated with Visual Analogue Scale-Anxiety (VAS-A) and with Panic Symptom List (PSL III-R). Respiratory parameters, heart rate and skin conductance were also recorded. Compared with placebo, vestipitant showed a significant reduction ( p <0.05) in anxiety assessed on the VAS-A scale (ΔVAS-A%) while alprazolam significantly ( p <0.01) attenuated the PSL III-R total score. Vofopitant did not show any anxiolytic effect. In the comparison analysis between placebo and drugs, none of the respiratory and other physiological parameters showed a statistically significant difference.